Interaction between Phosphorus and Nitrogen in Organomineral Fertilizer - Grohskopf, Marco Andre [UNESP]; Correa, Juliano Corulli; Fernandes, Dirceu Maximino [UNESP]; Teixeira, Paulo Cesar; Cruz, Caio Vilela [UNESP]; Almeida Mota, Sandra Camile (Taylor & Francis Inc, 2019)
The aim of this research is to assess the effect of the interaction between phosphorus and nitrogen (P???N) in organomineral fertilizer in the nutrition of plants cultivated in a Typic Hapludox. It was used a completely randomized design in a 5???5 factorial scheme with four replications. The treatments corresponded to the equivalent of five doses of P (0, 20, 40, 60, and 80 kg ha(?1) of P) in interaction with five doses of N (0, 50, 100, 150, and 200 kg ha(?1) of N). Three sequential crops of millet were carried out with 40?days of growth each, whose aerial part of the plants was harvested in order to determine the dry biomass and the contents of N and P. After each crop, soil samples were collected from the pot for determination of the forms of P and N. It may be inferred that simultaneous application of N and P into the fertilization does not promote significant changes in the dynamics of N in the soil, but the effect of the interaction is changed over the crop time in the plant. In soil the application of organomineral fertilizers did not show effect of the interaction between P ??N on the forms of organic N, inorganic and organic P, except for a difference in the available P, which is the dose of 20P???200N kg ha(?1) with greater efficiency. In the plant, there was interaction between P ??N in organomineral fertilizer on the dry biomass of the aerial part of millet from the dose of 20P???100N, focusing on the dose of 50P???150N kg ha(?1), while the accumulation of P and N starts from the dose of 40P???100N and 40P???50N kg ha(?1) with an increase (synergy) in both nutrients up to the dose of 80P???200N kg ha(?1).
Keywords: Poultry litter; fertilization; relationship among nutrients; effect